(untitled) (World Bulletin of Social Sciences, 2023)
This article is about the international transit system of Uzbekistan in Central Asia. Based on archival data, the author analyzed the problem based on the existing scientific literature and studied the existing specific aspects of the international transit system of Uzbekistan in Central Asia.